1996
DOI: 10.1002/hep.510240103
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Fecal Excretion of Hepatitis A Virus in Adult Patients With Hepatitis A As Determined by Polymerase Chain Reaction

Abstract: the most sensitive method for the detection of nucleic acids. 14 In hepatitis A virus (HAV) infection, fecal excretion ofA recent report on an outbreak of hepatitis A in a neonatal the virus has been reported to cease shortly after sympintensive care unit reported the occurrence of prolonged extoms occur. Although there have been several reports cretion of HAV RNA in stool (as long as 6 months) much on detection of HAV in feces using polymerase chain longer than previously reported. 15 However, neonates may re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 12 publications
(21 reference statements)
0
43
0
3
Order By: Relevance
“…Therefore, the detection of HAV-RNA in sera is practical and useful to study the molecular epidemiology of HAV infection. Nonetheless, HAV concentration in feces is usually higher than in sera and fecal shedding can persist for months after resolution of hepatitis (Yotsuyanagi et al, 1996). In fact, delayed fecal excretion of HAV is predominantly observed in neonates or young children, reflecting the importance of cell-mediated immunity in resolving the infection (Rosenblum et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the detection of HAV-RNA in sera is practical and useful to study the molecular epidemiology of HAV infection. Nonetheless, HAV concentration in feces is usually higher than in sera and fecal shedding can persist for months after resolution of hepatitis (Yotsuyanagi et al, 1996). In fact, delayed fecal excretion of HAV is predominantly observed in neonates or young children, reflecting the importance of cell-mediated immunity in resolving the infection (Rosenblum et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…15 In developed countries, a substantial number of patients with hepatitis A acquired HAV through homosexual activity (www.cdc.gov/nciod/diseases/hepatitis/ h96surve.htm). Recent studies using PCR analysis have shown that the fecal excretion of HAV continues even after recovery, 16 which suggests that hepatitis A patients may transmit the virus even after recovery. This is in accordance with the fact that positivity for anti-HAV among homosexual people is very high.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that HAV viremia regularly paralleled the clinical and biochemical course of the disease even in cases of relapsing disease (Sagnelli et al, 2003). Viremia was detectable for up to 490 days after the onset of icterus and was correlated with elevated transaminases but not with anti-HAV (Normann et al, 2004) RNA was detected in stools up to 3 months after the onset of clinical symptoms, in one case even after alanine aminotransferase (ALT) levels fell to normal (Yotsuyanagi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%